Tiktok workshop for teaching, learning and entrepreneurship / Dr. Hanish Singh Jayasingh Chellammal and Assoc. Prof. Dr. Mahmathi Karuppannan - Jayasingh Chellammal, Hanish Singh; Karuppannan, Mahmathi (Faculty of Pharmacy, 2023)
On 15th March 2023, CPD team of the Faculty of Pharmacy, UiTM organised a TikTok workshop for teaching, learning and entrepreneurship. The workshop was held at DK4, FF4 Block, UiTM Puncak Alam campus and was prospected by Dr Norkasihan Ibrahim, the Deputy Dean of Industry, Community and Alumni Network (ICAN), Faculty of Pharmacy, UiTM. The program aimed to provide knowledge and training on the application of TikTok in teaching, learning and as a tool for entrepreneurship among the Medical, Dental, Pharmaceutical and other health science experts.